Transfer of financial risk in emerging eastern European stock markets: A sectoral perspective - Elena Fedorova (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
With the rise of interconnected global financial systems, there is an increased risk that a financial crisis in one country may spread to others. The contagion effects of the 2008 global financial crisis hit advanced economies fast and hard while sparing less developed and less integrated financial systems. The present study focuses on the contagion effects at Eastern European stock markets and changes in their interconnections after EU accession in 2004. Specifically, we investigate the relationship among the stock market sectors of Poland, Hungary and the Czech Republic during 1998-2009 and their exposure to on-shored financial risk. The evidence suggests direct linkages between different stock market sectors with respect to returns and volatilities with increased equity-shock transmission between markets after EU accession in 2004. Of particular note is the intra-industry contagion in emerging Europe. Our findings have implications for asset pricing and portfolio selection for international financial institutions and financial managers.
URN:NBN:fi:bof-201408072214
Keywords: 330